FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SUSU FORMULA ANAK (BALITA) DI KOTA MALANG - K S. Suroto; Z. Fanani; B A. Nugroho (Universitas Tribhuwana Tunggadewi, 2012)
Various brands of formula milk offered by many companies make mothers having under five year old children difficult to make decision to buy formula milk. The purposes of this study were to analyze the simultaneous and partial effects of cultural, social, personal, psychological, product and price variables on buying decision of formula milk, and to analyze the variables having dominant influence on the purchasing decisions of formula milk at Malang City. This study was conducted at Lowokwaru, Kedungkandang, Blimbing, Sukun and Klojen Districts of Malang City from November to December 2012. The method used for this study was an explanatory survey method using questionnaires to collect data from 120 mothers having under five year old children consuming formula milk that were selected by an accidental sampling method. Data of respondents were measured using Likert Scale that ranged from 1 (strongly disagree) to 5 (strongly agree). A multiple linear regression model was used to predict the effects of culture (X1), social (X2), personal (X3), psychological (X4), product (X5) and price (X6) variables on purchasing decision (Y). The results showed that the six variables simultaneously affected significantly the purchasing decision of formula milk at Malang City. The six variables contributed 83.5% of the variation in formula milk purchasing decision. Partially, cultural, social, personal, psychological, and product variables positively influenced the purchasing decisions of formula milk, while price variabels did not significantly influence the purchasing decision of formula milk. Cultural variable was the most dominant variable affecting purchasing decision of formula milk